2000
DOI: 10.1111/j.1553-2712.2000.tb02229.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hypertension on the Response to Blood Loss in a Rodent Model

Abstract: Abstract.Objective: Hypertensive patients having higher baseline peripheral resistance and sympathetic tone than normotensive patients may have aberrant responses to hemorrhage. In an attempt to further characterize this clinical observation, the authors compared the hemodynamic and metabolic responses to hemorrhage between spontaneously hypertensive rats (SHR) and normotensive rats (NTR). Methods: Twenty adult rats (10 NTR and 10 SHR) were anesthetized with althesin via the intraperitoneal route. Femoral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…[4][5][6][7][8] At the level of vascular injury, hemorrhage volume may be limited in hypertensives by their higher vascular resistance 19 and a hypercoagulable state. 20 Higher vascular resistance and increases in coagulation may also explain hypertensives' greater sensitivity to blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] At the level of vascular injury, hemorrhage volume may be limited in hypertensives by their higher vascular resistance 19 and a hypercoagulable state. 20 Higher vascular resistance and increases in coagulation may also explain hypertensives' greater sensitivity to blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…A defect in the both the afferent and efferent limbs of the baroreflex response to blood loss has been documented in the SHR. [4][5][6][7][8] At the level of vascular injury, hemorrhage volume may be limited in hypertensives by their higher vascular resistance 19 and a hypercoagulable state. 20 Higher vascular resistance and increases in coagulation may also explain hypertensives' greater sensitivity to blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent experiment in our laboratory using a catheter-controlled hemorrhage model showed a more profound hemorrhagic shock insult in the SHR group as compared with normotensive Wistar-Kyoto rats (WKYs) after the same volume of blood loss. 6 A catheter-controlled hemorrhage model cannot completely describe hemorrhage from a vascular injury. Unlike a catheter-controlled hemorrhage, a vascular injury results in an uncontrolled hemorrhage with the potential for continued blood loss.…”
mentioning
confidence: 99%
“…Another study also demonstrated that hypertensive animals experienced more profound hemorrhagic shock compared with nor-motensive animals 15 . In this study, we used uncontrolled hemorrhagic shock model.…”
Section: Discussionmentioning
confidence: 94%
“…Experimental and clinical studies indicated that there is a defect in hemodynamic and baroreflex responses after hemorrhage in hypertensive subjects 6 . Furthermore, hypertensive animals have greater tissue ischemia such as liver, skeletal muscles and brain than normotensive 15 . Several circulating factors such as NO are involved in modulation of cardiovascular response to hemorrhagic shock 7 .…”
Section: Discussionmentioning
confidence: 99%